An investigation into the association between asthma, osteoporosis, and fractures using electronic health records - Chalitsios, Christos (2021)
This doctoral thesis aims to understand the current burden and risk of osteoporosis and fragility fractures in asthma and as related to asthma treatment as well as the association between the use of bisphosphonates (medications that reduce the risk of osteoporosis) and the risk of subtrochanteric and femoral shaft fractures in asthma to provide bone protection guidance for clinicians and policy makers improving patients’ quality of life.